Actantial Insights: Making Sense of Sport for Development Performance Account Management. Issue 2 (18th May 2022) - Webb, Andrew
Abstract: The purpose of this paper is to improve one proven method for understanding the management of performance accounts. This is important as there is currently a need for obtaining insights on how, what, and why performance accounts are used in both for profit and non-profit organisations in general, as well as in the more specific field of sport for development. To this end, I propose to add a second move to how previous management research operationalised Greimas and Courtés' actantial model. A case study that 'test-drives' the two combined moves completes this study and raises important ethical questions regarding the translation of readers into actors through manipulation and sanctioning.